Functional Recovery and Life Satisfaction in the First Year After Severe Traumatic Brain Injury. Issue 4 (July 2015) - Anke, Audny; Andelic, Nada; Skandsen, Toril; Knoph, Rein; Ader, Tiina; Manskow, Unn; Sigurdardottir, Solrun; Røe, Cecilie
<x xml:space="preserve">Abstract</x> Objectives: (1) To examine the impact of demographic and acute injury-related variables on functional recovery and life satisfaction after severe traumatic brain injury (sTBI) and (2) to test whether postinjury functioning, postconcussive symptoms, emotional state, and functional improvement are related to life satisfaction. Design: Prospective national multicenter study. Setting: Level 1 trauma centers in Norway. Participants: 163 adults with sTBI. Main Measures: Functional recovery between 3 and 12 months postinjury measured with Glasgow Outcome Scale Extended, Rivermead Postconcussion Symptoms Questionnaire, Hospital Anxiety and Depression Scale, and satisfaction with life situation. Results: 60% of cases experienced functional improvement from 3 to 12 months postinjury. Multivariate logistic regression analysis revealed that discharge to a rehabilitation department from acute care (odds ratio [OR] = 2.14; P < .05) and fewer days with artificial ventilation (OR = 1.04; P < .05) were significantly related to improvement. At 12 months postinjury, 85% were independent in daily activities. Most participants (63%) were satisfied with their life situation. Regression analysis revealed that older age (>65 years), low education, better functional outcome, and the absence of depressive and postconcussion symptoms were significant (P < .05) predictors of life satisfaction. Functional improvement was significantly associated with emotional state but not to life satisfaction. Conclusion: Following sTBI, approximately two-thirds of survivors improve between 3 and 12 months postinjury and are satisfied with their life. Direct discharge from acute care to specialized rehabilitation appears to increase functional recovery.